L‐type amino acid transporter 1 expression in esophageal carcinogenesis according to WHO and Japanese classifications of intraepithelial neoplasia. Issue 5 (29th March 2017) - Hashimoto, Hirotsugu; Kurata, Atsushi; Kikuchi, Hiroyuki; Masuda, Yoshio; Fujita, Koji; Okuyama, Rikiya; Inoue, Shigeru; Horiuchi, Hajime; Kuroda, Masahiko
Abstract : L‐type amino acid transporter 1 (LAT1) has an essential role in cell proliferation especially in neoplasms. Although immunohistochemical expression of LAT1 has been investigated in invasive esophageal carcinoma, its expression in intraepithelial neoplasia (IEN) has not been reported. Further, classification of esophageal IEN is currently different between the World Health Organization (WHO) and Japanese criteria. Therefore, in this study, immunohistochemical expressions of LAT1 along with Ki‐67 were analyzed in 66 esophageal samples of endoscopic submucosal dissection. Extension of cells positive for either marker within the epithelium, along with LAT1 intensity at the base of the epithelium, was evaluated. The results among early IENs, progressed IENs, and invasive carcinoma based on both WHO and Japanese criteria were compared. It was demonstrated that Ki‐67 + cells extended toward the superficial layer in IENs, which was more pronounced in progressed compared with early IENs based on both WHO and Japanese criteria. Although similar results were obtained for LAT1 + cells, LAT1 + cell extended more in invasive carcinoma than in progressed IENs according to the WHO criteria. Further, LAT1 intensity was different between early and progressed IENs based on the Japanese criteria alone. Thus, use of LAT1 immunohistochemistry and Japanese classification may be more meaningful to characterize esophageal carcinogenesis.